Metal-free synthesis of 3-thiocyanatobenzothiophenes by eosin Y photoredox-catalyzed cascade radical annulation of 2-alkynylthioanisoles - Tambe, Shrikant D.; Jadhav, Mahesh S.; Rohokale, Rajendra S.; Kshirsagar, Umesh A. (European Journal of Organic Chemistry, 2018)
A convenient, efficient, metal-free synthesis of 3-thiocyanatobenzothiophenes has been developed that uses eosin Y in a visible-light-mediated photoredox-catalyzed anion oxidation of the ammonium salt of thiocyanate and proceeds through the cascade radical annulation of 2-alkynylthioanisole at room temperature. The present protocol requires visible light as a green energy source, an organic dye as the photocatalyst, and oxygen as a green oxidant to provide a mild route with a broad substrate scope for the formation of potentially bioactive 3-substituted benzothiophene derivatives in good yields.